Perancangan Toko Online UMKM dengan OpenCart untuk Meningkatkan Daya Saing di Kec. Sijunjung - Rizki Akbar, Danu; Annas, Firdaus; Fadila, Nurul (Yayasan Lembaga Studi Makwa, 2024)
Advances in digital technology provide great opportunities for Micro, Small and Medium Enterprises (MSMEs) to increase their competitiveness in local and global markets. However, unfortunately there are still many MSMEs in Sijunjung District that have not utilized digital platforms optimally so that their market reach is only limited to the Sijunjung area and does not reach areas outside it. This is very unfortunate because consumers from other areas may want the products sold by these MSMEs. Therefore, this research aims to design an OpenCart-based online shop as a solution for MSMEs to expand market reach and increase operational efficiency and simplify the buying and selling transaction process. The research method used is Research and Development (R&D) with stages including needs analysis, system design, implementation, and evaluation of the final product. The research results show that the OpenCart platform can be adapted to meet the specific needs of MSMEs, such as ease of product management, flexible payment features, and an attractive and responsive display. Evaluation of the system shows an increase in the potential competitiveness of MSMEs through wider access to digital markets and more structured business management. By implementing this online shop, MSMEs in Sijunjung District can be better prepared to compete in the digital era and increase income in a sustainable manner. This research makes a real contribution in empowering MSMEs through digital technology and becomes a model for developing MSMEs in other regions.